Stress of Type 2 Diabetes Mellitus Patients in Implementation Self Care Management - Setyorini, Andri; Supriyadi, Supriyadi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Diabetes has now become a common disease and we can find it anywhere. DM disease cannot be cured, but it can be managed by complying with the 4 pillars of DM management which should ideally be carried out properly. This certainly can lead to boredom and stress because they have to comply with the recommended DM management program throughout their life. The purpose of this study is to explore the description of stress in patients with type 2 diabetes in the implementation of self-care management. This study uses a descriptive qualitative and data collection techniques use in-depth interviews.Participants in this study were 5 DM type 2 patients using purposive sampling technique. Data analysis used qualitative content analysis. The results of the study are four main themes that illustrate stress in patients with type 2 diabetes in the implementation of self-care management including: perceived complaints, comorbidities, dietary restrictions, and psychosocial factors.